2019
DOI: 10.1039/c8cc10283j
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide membranes with narrow inter-sheet galleries for enhanced hydrogen separation

Abstract: Brodie's GO sheets are prepared, characterized and compared to Hummers’ GO sheets. GO-B membranes are synthesized on polyester substrates using filtration. Permeability reduction of large gas molecules (CH4, N2 and CO2) is more significant compared to permeability reduction of small gas molecules (H2 and He). Pressure filtration enhances the packing density of GO-B sheets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Apparently, the main mechanism for large molecules (CH 4 , N 2 , and CO 2 ) is Knudsen diffusion, since the interlayer distance is rather large. This is confirmed by experimental datathe permeability of these gases is inversely proportional to the square root of the molecular weight [89,90,92]. However, the substantially higher permeability for hydrogen and helium indicates that another path contributes additionally.…”
Section: Graphene-based Membranes For the Purification And Concentratsupporting
confidence: 72%
See 1 more Smart Citation
“…Apparently, the main mechanism for large molecules (CH 4 , N 2 , and CO 2 ) is Knudsen diffusion, since the interlayer distance is rather large. This is confirmed by experimental datathe permeability of these gases is inversely proportional to the square root of the molecular weight [89,90,92]. However, the substantially higher permeability for hydrogen and helium indicates that another path contributes additionally.…”
Section: Graphene-based Membranes For the Purification And Concentratsupporting
confidence: 72%
“…Owing to its unique thin-layered structure and the presence of functional groups, membranes based on graphene oxide (GO membranes) can also provide high permeability and selectivity and can be used in practice for hydrogen purification or hydrogen evolution [66,67,73,79,[86][87][88][89][90][91][92][93]. The homogeneous layered structures required to form membranes can be obtained from dispersions of GO flakes by dip coating, vacuum filtration, spray coating, layer-by-layer deposition, and other methods.…”
Section: Graphene-based Membranes For the Purification And Concentratmentioning
confidence: 99%
“…It has been proposed that the interlayer spaces of GONs are the main channels for the transport of both gas and liquid molecules in GO membranes. [10] Meanwhile,t he good me- (3.5 6.0 ). b) MOF structure viewed along b axis highlighting the nonporous wall of the 1D channels along a axis.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that GO-B membranes can be fabricated with a much smaller interlayer spacing (6.0 Å) in comparison to GO-H, leading to more effective molecular sieving. From the gas permeation testing [ 98 ], the increases in H 2 /CO 2 , H 2 /N 2 and H 2 /CH 4 selectivities by 129%, 91% and 76%, respectively, were reported when GO-B was employed in the membrane fabrication instead of GO-H. However, it should be noted that this synthesis protocol is more complicated and tedious as compared to the Hummer’s method, since repetitive graphite oxidation is required (typically about three ~ four times) to obtain the desired product (C/O ratio > 2).…”
Section: Performance Of a Graphene-based Membranementioning
confidence: 99%